2004
DOI: 10.1002/nau.20066
|View full text |Cite
|
Sign up to set email alerts
|

Motor evoked potentials (MEP) and evoked pressure curves (EPC) from the urethral compressive musculature (UCM) by functional magnetic stimulation in healthy volunteers and patients with neurogenic incontinence

Abstract: MEP and EPC from the UCM proved to be a well tolerated disgnostic tool in patients with neurogenic incontinence that distinguished central and peripheral lesions of the motor efferent pathways to the UCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 53 publications
0
3
2
Order By: Relevance
“…Currently, SMS causes a significant increase in bladder capacity, which could be due to acute activation of the inhibitory reflex pathway to the detrusor induced by stimulation of pudendal afferents. Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated . However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Currently, SMS causes a significant increase in bladder capacity, which could be due to acute activation of the inhibitory reflex pathway to the detrusor induced by stimulation of pudendal afferents. Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated . However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, recent studies have shown that SMS stimulates mainly sensory afferent fibers and the urethral responses are reflexively mediated. 6,18,19 However, in this study duloxetine, which works at the level of Onuf's nucleus, did not change amplitudes of pressure spikes in response to SMS, suggesting that the pressure spikes were unlikely to be reflex urethral responses via the afferent pathways. It is, thus, conceivable that SMS conducted in this study may be direct stimulation of only efferent fibers to external urethral sphincter.…”
Section: Discussioncontrasting
confidence: 65%
“…This method can also be used to test EAS motor efferents . However, until now, EAS‐EPCs have only been studied in healthy subjects and in patients with known spinal cord lesions . To our knowledge, the results of EAS‐EPCs have never been reported in a population of patients with FI.…”
Section: Discussionmentioning
confidence: 99%
“…facilitory preinnervation) to study the influence of muscle facilitation on the motor response. High‐intensity stimulations were deliberately chosen because it has been shown that the energy required to evoke a MEP response is higher than that required to provoke the muscles of the extremities . We asked the subjects to perform a maximal voluntary contraction because, unlike muscles of the extremities, it is often difficult for incontinent patients to modulate anal sphincter contractions and perform a slight or mild contraction .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation